(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This article analyzes language as a means of communication and transmission of information, and also examines speech as a process of producing sounds and forming words and phrases. In addition, the connection between language and speech and their originality for human communication is of particular interest